(untitled) (Journal of Hama University, 2021)
This research was conducted to determine the effect of using the transportation method in improving the competitive advantage in its five dimensions (quality, cost, flexibility, speed and delivery, creativity and innovation) in a sample of the Syrian industrial companies. The researcher distributed (110) questionnaires to a sample of managers, department heads, and members of the administrative cadres responsible for taking different forms and types of administrative decisions in the companies under study. (103) questionnaires were retrieved, and (9) were excluded from them for not completing their data. Thus, the number of completed questionnaires was (94). The researcher analyzed the data using the Statistical Analysis Program (SPSS 25). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect of using the transportation method in improving the competitive advantage in its five dimensions (quality, cost, flexibility, speed and delivery, creativity and innovation) in the companies under study.